The Diversion Completion Based on Law Number 11 of 2012 Concerning the Juvenile Criminal Justice System from the Perspective of Islamic Law - Ilmi, Jamiatul; Hidayat, M. Rahmat; Maslyna, Ika (PT ARRUS Intelektual Indonesia, 2023)
This study aims to implement the diversion in Law Number 11 of 2012 concerning the Juvenile Criminal Justice System in the Court of Bengkalis Regency and the perspective of Islamic law. This type of research is normative research. Data collection methods employed interviews and documentation. The data analysis technique used qualitative analysis. The results of the study indicate that the implementation of diversion according to the perspective of Islamic law regarding the diversion of Juvenile cases based on Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, among others, in Islamic law, there is no normative evidence regarding criminal sanctions, especially in the form of imprisonment for children. This is because Criminal punishment sanctions for children in Islam are ta'dib (education) which is regulated by the waliyul amri (leader).